Analysis of the foundations of market gardening activity in the Commune of Athiémé (Benin) - MONDE, Marcelle Agathe; Ahouangninou, Claude; ABDOULAYE, DJAFAROU; KIKI, Yawo Denis Landry; MASSEDE, Samuel; TENTE, AGOSSOU BRICE HUGUES (My University, 2023)
Vegetable production has been a booming activity in Benin for several years, as in most countries of the West African region. The Beninese state and many other organizations are working together to develop this activity, create jobs and strengthen food security in the country. In rural areas, this agricultural sub-sector is considered one of the important measures to guarantee food security and promote income diversification. However, questions arise about the viability of this form of activity. This study aims to analyze market gardening operations in the Commune of Athiémé in Benin. To achieve this objective, different data collection techniques are used, namely documentary research, observation, interviews and questionnaire surveys with market gardeners and an interview guide administered to local authorities. A sample of 206 market gardeners is questioned. The socio-demographic data of market gardeners and agricultural statistics (areas, production and yields, etc.) are collected. The results obtained showed that market garden production is a highly developed activity in the Commune of Athiémé and is practiced at all times of the year. The most developed methods of accessing land are by inheritance (31.9%) and by purchase (31.9%). Family labor was used most often on market gardening farms (76.21%). For water supply to farms, the dominant systems were those relating to irrigation, the use of rainwater and floodwater. The basic water distribution or irrigation equipment was motor pumps, which as used by 93.57% of market gardeners. For the fertilization, the majority of market gardeners prefer the use of Urea (44.44%) and NPK (35.28%). Only 10.83% use cow purse and poultry dung. For the control of crop pests and diseases, producers use a variety of chemical pesticides. Improved production systems, including training for producers, improved irrigation systems, soil fertilization and plant protection measures will promote the sustainability of vegetable farms.
Keywords: Analysis; vegetable farm; production system; vegetable crops; Athiémé